Black Rice Extract Reduces Body Weight, Waist Circumference, Body Mass Index and Lipopolysaccharide in Obese Subjects: A Preliminary Study - Makmun, Armanto; Bukhari, Agussalim; Taslim, Nurpudji Astuti; Aminuddin, Aminuddin; Sandra, Ferry (The Indonesian Biomedical Journal, 2024)
BACKGROUND: The prevalence of obesity, or an excessive fat accumulation, is keep increasing. In obesity, inflammation can be induced by leaky gut due to the intestinal tight junction barrier dysfunction. Zonula occludens-1 (ZO-1) plays a role in developing intestinal tight junction barrier dysfunction and gut microbiota imbalance, thus promote the translocation of bacterial endotoxin characterized by lipopolysaccharide (LPS) into circulation. Black rice extract (BRE) has been known to have anti-inflammatory property. This study was conducted to investigate the effect of BRE on body weight (BW), waist circumference (WC), body mass index (BMI), ZO-1 and LPS of obese patients.METHODS: Twenty-three male subjects were divided into non-obese group (NOG), obese group (COG) and BRE-obese group (BOG). Subjects in BOG received a daily dose of 5.6 g/day BRE for 4 weeks. BW, WC and BMI, serum ZO-1 and LPS were measured before and after treatment.RESULTS: BRE was prepared successfully and free from microbial contamination. Treatment of BRE for 4 weeks reduce BW (95.40±5.78 vs. 94.59±6.00 kg, p=0.043), WC (109.25±3.55 vs. 107.50±3.46 cm, p=0.000) BMI (32.65±1.86 vs. 32.18±1.80, p=0.000) and LPS (222.27±38.63 vs. 131.63±9.70 ng/mL, p=0.020) of obese subjects. The pre-post ZO-1 levels in all groups were not significantly different (p>0.05).CONCLUSION: Treatment of 5.6 gr BRE daily for four weeks can reduce BW, WC, BMI and serum LPS, but not serum ZO-1 in obese patients. Therefore, BRE may reduce inflammation in obesity.KEYWORDS: black rice, obesity, BW, WC, BMI, LPS, ZO-1